The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1590/s0100-879x2006000700017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mercury intoxication on the response of horizontal cells of the retina of thraira fish (Hoplias malabaricus)

Abstract: Methyl mercury (MeHg) is highly neurotoxic, affecting visual function in addition to other central nervous system functions. The effect of mercury intoxication on the amplitude of horizontal cell responses to light was studied in the retina of the fish Hoplias malabaricus. Intracellular responses were recorded from horizontal cells of fish previously intoxicated with MeHg by intraperitoneal injection (IP group) or by trophic exposure (T group). Only one retina per fish was used. The doses of MeHg chloride admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
(35 reference statements)
0
15
0
4
Order By: Relevance
“…There is some evidence that tropical fish have a much faster uptake of mercury and a higher bio-accumulation factor (Oliveira Ribeiro et al 2000). Tanan et al (2006) reported effects on the retina of the tropical Hoplias malabaricus at methylmercury levels that may be encountered in the field. Possible effects from mercury on the fish population of the PWS area are not visible at present; the CI AquaRAP ichthyologists described the fishes as being ''in excellent condition; the predators such as S. rhombeus and H. aimara were abundant and of very large size; the colors of the ornamental fishes were brilliant; there were almost no parasites or infections found on the fishes'' (Mol et al 2006).…”
Section: Conservation Considerationsmentioning
confidence: 99%
“…There is some evidence that tropical fish have a much faster uptake of mercury and a higher bio-accumulation factor (Oliveira Ribeiro et al 2000). Tanan et al (2006) reported effects on the retina of the tropical Hoplias malabaricus at methylmercury levels that may be encountered in the field. Possible effects from mercury on the fish population of the PWS area are not visible at present; the CI AquaRAP ichthyologists described the fishes as being ''in excellent condition; the predators such as S. rhombeus and H. aimara were abundant and of very large size; the colors of the ornamental fishes were brilliant; there were almost no parasites or infections found on the fishes'' (Mol et al 2006).…”
Section: Conservation Considerationsmentioning
confidence: 99%
“…42,43 Furthermore, retinal damage has been found in methylmercury intoxication as a reduction of the density in amacrine and bipolar cells, and alterations of the horizontal cells by electrophysiological measurements. 44,45 In humans exposed to Hg vapor, electrophysiological evidence for impairment of the peripheral retina has been found in full-field electroretinogram responses, and in the central retina by multifocal electroretinogram responses. 5 The authors argued that the involvement of the central retina, in addition to the retinal periphery, was in line with psychophysical results showing losses of central visual functions (luminance spatial contrast sensitivity and color vision), 5 confirmed by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…7.5b mostra uma dessas imagens. Para cada imagem os colaboradores identificaram as coordenadas espaciais dos neurônios com a ajuda do software NIH Scion No caso da intoxicação por baixas doses, outros trabalhos descrevem que ocorre um aumento da resposta eletrofisiológica nas células horizontais [65] e também um pequeno aumento no número de células [6]. Nesses casos, não ocorrem alterações significativas no arranjo espacial das células da retina, conforme demonstrado peloíndice de hexagonalidade.…”
Section: Análise Da Hexagonalidade Em Retinas De Hoplias Malabaricusunclassified